Реорганизация ремонтной службы машиностроительного предприятия в рамках внутреннего экономического механизма - Еськов, А.Л.; Беличенко, Н.А. (Економічний вісник Донбасу, 2011)
In this article an objective picture of discrepancy of the level of technique facilities, engineering and reengineering of bussiness processes of the basic production to the technique base, equipment and to the qualification level of employees of auxilary services of enterprises in the field of machine-building has been considered. On the basis of this analysis diadvantages of repair service of ZAO NKMZ, particulary oganazing and menegement disagvantages heve been investigated and it has been proposed to ctntialize the repair service into the separate expenditure centre. It will allow to define propely the functions and duties of each subdivision, to determine the mechanizm of their activity evaluation and to propose an active motivation mechanism for the workers. Key words: reorganization, mechanism, repair, service.